Optimum take-off techniques and muscle design for long jump - Seyfarth, A.; Blickhan, R.; van Leeuwen, J. L. (2000)
A two-segment model based on Alexander (1990; Phil. Trans. R. Soc. Lond. B 329, 3-10) was used to investigate the action of knee extensor muscles during long jumps. A more realistic representation of the muscle and tendon properties than implemented previously was necessary to demonstrate the advantages of eccentric force enhancement and non-linear tendon properties. During the take-off phase of the long jump, highly stretched leg extensor muscles are able to generate the required vertical momentum. Thereby, serially arranged elastic structures may increase the duration of muscle lengthening and dissipative operation, resulting in an enhanced force generation of the muscle-tendon complex. To obtain maximum performance, athletes run at maximum speed and have a net loss in mechanical energy during the take-off phase. The positive work done by the concentrically operating muscle is clearly less than the work done by the surrounding system on the muscle during the eccentric phase. Jumping performance was insensitive to changes in tendon compliance and muscle speed, but was greatly influenced by muscle strength and eccentric force enhancement. In agreement with a variety of experimental jumping performances, the optimal jumping technique (angle of attack) was insensitive to the approach speed and to muscle properties (muscle mass, the ratio of muscle fibre to tendon cross-sectional area, relative length of fibres and tendon). The muscle properties also restrict the predicted range of the angle of the velocity vector at take-off. J Exp Biol 2000 Feb;203 Pt 4:741-50